7th International Conference on Remote Engineering & Virtual Instrumentation - for Papers, Call (International Journal of Online and Biomedical Engineering (iJOE), 2009)
REV 2010 is the seventh in a series of annual events concerning the area of remote engineering and virtual instrumentation. The REV conferences are the annual conferences of the International Association of Online Engineering (IAOE) (www.online-engineering.org). REV2010 will be held at Kungliga Tekniska Högskolan (Royal Institute of Technology, KTH) in Stockholm. The general objective of this conference is to demonstrate and discuss fundamentals, applications and experiences in the field of remote engineering and virtual instrumentation. With the globalization of education the interest in and need of teleworking, remote services and collaborative working environments now increases rapidly. Another objective of the symposium is to discuss guidelines for education in university level courses for these topics. REV 2010 offers an exciting technical program as well as academic networking opportunities during the social events.